Fulfillment of the Right to Disclosure Information in Realizing Good Governance - Mahdy Muhana Azis; Rini Triastuti; Dewi Gunawati (International Journal Labs, 2022)
This study would like to reveal the implementation and strategies used by public officials in the policy process related to dam construction in Lampung Province. The research method used is qualitative with a descriptive analysis approach. Within the scope of Lampung Province, the policy of the Kementerian Pekerjaan Umum dan Perumahan Rakyat (PUPR) through the Balai Besar Wilayah Mesuji-Sekampung (BBWS) is to complete the construction of the Margatiga Dam, one of its duties is to ensure the implementation of public and legal communications as well as complaints from the local community. The study results indicate that information disclosure has been seen in planning and performance transparency. This is evidenced by the involvement of the community through indigenous community forums, community coordination with implementing public relations, and holding socialization for each village.